Nutritional and physical exercise programs for older people: program format preferences and (dis)incentives to participate - Dedeyne L; Dewinter L; Lovik A; Verschueren S; Tournoy J; Gielen E (Clinical Interventions in Aging, 2018)
Lenore Dedeyne,1 Louise Dewinter,1 Aniko Lovik,2 Sabine Verschueren,3 Jos Tournoy,1,4 Evelien Gielen1,4 1Department of Chronic Diseases, Metabolism and Ageing, KU Leuven – University of Leuven, Leuven, Belgium; 2L-BioStat, KU Leuven – University of Leuven, Leuven, Belgium; 3Department of Rehabilitation Sciences, KU Leuven – University of Leuven, Leuven, Belgium; 4Department of Geriatric Medicine, University Hospitals Leuven, Leuven, Belgium Purpose: A growing number of studies in older people have been examining the beneficial effects of non-pharmacological interventions, such as physical exercise (PE) and nutritional supplementation, to target age-related syndromes such as sarcopenia and frailty. This study evaluated interpersonal, intrapersonal, and community (dis)incentives, concepts of motivation, and preferred program formats toward a PE or nutritional program in older people, with or without frailty or risk of sarcopenia. Methods: A questionnaire was developed and filled in by 115 community-dwelling older adults (≥65 years of age) after content (n=7 experts) and face validation (n=8 older adults). We assessed 1) the agreement with a statement (a statement with which ≥70% of the participants agree or strongly agree is considered as a common statement), 2) concepts of motivation by an exploratory factor analysis, and 3) program preferences by nonparametric Wilcoxon or Friedman’s analysis of variance and post hoc Wilcoxon signed-rank tests. Results: Intrapersonal motivators (eg, health benefits) were the most common motivators to participate in a PE or nutritional program. Identified concepts to participate in a PE intervention were intrinsic health beliefs, fear of falling or injuries, influence of significant others and environment, and (para)medical encouragement (Cronbach’s alpha: 0.75; 72% variance explained). Intrinsic health beliefs, influence of significant others and (para)medical encouragement were identified as concepts that motivate older people to participate in a nutritional intervention (Cronbach’s alpha: 0.77; 78% variance explained). No favorability of exercise location was identified; however, older people preferred protein supplement intake in a tablet form compared to liquid or powder form and in a pulsed timing compared with a spread intake. Conclusion: Program preferences of older people toward nutritional interventions need to be taken into account in future clinical trials and implementation programs, to increase recruitment and adherence to interventions. Keywords: physical activity, nutrition, incentives, sarcopenia, frailty, old